Preparation method of aluminum alloy for energy storage shell
By smelting and treating aluminum alloys with ceramic fibers and silicon dioxide nanoparticles, the method addresses low strength and thermal conductivity issues, resulting in improved mechanical and thermal performance for energy storage shells.
Patent Information
- Application Number
- CN202411195127.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing aluminum alloys used in energy storage shells suffer from low strength and poor thermal conductivity, complicating production and failing to meet industry requirements for lighter and more durable battery packs.
A method involving smelting, extrusion, and aging of aluminum alloys with a composite material containing ceramic fibers and silicon dioxide nanoparticles, combined with a silane coupling agent and hexadecyltrimethylammonium bromide to enhance mechanical properties and thermal conductivity.
The method significantly improves the thermal conductivity and mechanical strength of the aluminum alloy, meeting the demands for energy storage shells by enhancing dispersibility and reducing agglomeration.
Smart Images

Figure BDA0005016146470000081 
Figure BDA0005016146470000091
Abstract
Description
Technical Field
[0001] The present invention relates to the field of aluminum alloy preparation, and in particular to a method for preparing an aluminum alloy for an energy storage shell. Background Art
[0002] Energy storage refers to the process of storing energy through a medium or device and releasing it when needed. According to the energy storage method, lithium-ion battery energy storage is very popular, and the battery needs an external protective box to prevent bumps and collisions during transportation, prevent water seepage, and have external flame retardant protection. The choice of aluminum alloy material not only reduces the risk of deformation and plays an appropriate protective role, but in order to make the battery pack lighter, the industry's requirements for energy storage materials are constantly increasing, and energy storage products are constantly innovating.
[0003] In the prior art, battery shells for energy storage are generally formed by stamping, using a punch press and a hydraulic press to punch out aluminum plates, stretch them 7-8 times, and temper them to remove stress. The production process is complicated and long, and the prepared aluminum alloy also has the problems of low strength and poor thermal conductivity, which cannot meet the use requirements. Summary of the invention
[0004] Based on this, in order to solve the problems of low strength and poor thermal conductivity of aluminum alloys in the prior art, the present invention provides a method for preparing aluminum alloy for energy storage housing, and the specific technical scheme is as follows:
[0005] A method for preparing an aluminum alloy for an energy storage housing, the method comprising the following steps:
[0006] The aluminum alloy raw material is subjected to a first smelting process, and then the composite material is added, subjected to a second smelting process, and then cast into an ingot;
[0007] The ingot is subjected to extrusion treatment, stretching treatment and aging treatment to obtain an aluminum alloy for an energy storage shell;
[0008] The surface of the aluminum alloy profile is loaded with nanoparticles, and the nanoparticles have nanopores with a pore size of ≤50nm; the nanoparticles are a composite material, and the raw materials for preparing the composite material include ceramic fibers and silicon dioxide in a mass ratio of (1-5): (1-7).
[0009] Furthermore, the aluminum alloy raw material includes the following chemical components in mass percentage: Si: 0.2%~0.5%, Fe: 0.10%~0.14%, Cu: 0.1%~0.3%, Mn: 1.0%~1.2%, La: 0.01%~0.03%, Zn: ≤0.1%, single impurity ≤0.05%, total impurities ≤0.15%, and the balance is aluminum.
[0010] Furthermore, the temperature of the first smelting treatment is 720° C. to 780° C., and the time is 10 min to 15 min.
[0011] Furthermore, the temperature of the second smelting treatment is 700° C. to 750° C., and the time is 1 min to 5 min.
[0012] Furthermore, the casting temperature is 650°C to 700°C, the casting speed is 35mm / min to 45mm / min, the casting cooling water pressure is 0.05MPa to 0.1MPa, and the cooling water temperature is 20°C to 25°C.
[0013] Furthermore, the extrusion barrel temperature of the extrusion process is 435°C to 450°C, and the extrusion die heating temperature is 490°C to 510°C.
[0014] Furthermore, the reduction rate of the stretching treatment is 40% to 45%.
[0015] Furthermore, the aging treatment is carried out at a temperature of 160±5°C and for a time of 8h to 10h.
[0016] Furthermore, the preparation method of the composite material is: adding a mixture of ceramic fiber and silicon dioxide to a silane coupling agent, stirring evenly, adding hexadecyltrimethylammonium bromide, performing ultrasonic oscillation treatment, then controlling the temperature to 45°C to 65°C, standing for 1h to 2h, and then filtering, drying the solid at 65°C to 85°C for 15min to 30min, calcining at 500°C to 600°C for 1h to 3h, and obtaining the composite material after ball milling.
[0017] Furthermore, the ultrasonic oscillation treatment has a time of 10 min to 15 min, a frequency of 25 kHz to 30 kHz, and a power of 50 W to 70 W.
[0018] In the above scheme, by adding the composite material to the aluminum alloy melt and limiting the main components of the composite material to ceramic fiber and silicon dioxide, it can be combined with the aluminum alloy and extend to the surface of the aluminum alloy profile, which can not only significantly increase the thermal conductivity of the aluminum alloy, but also help to improve the strength of the aluminum alloy. On the other hand, the composite material prepared in the present application, after being treated with a silane coupling agent and hexadecyltrimethylammonium bromide, can reduce the agglomeration between components, improve dispersibility, and improve the mixing uniformity with the aluminum alloy melt, thereby improving the mechanical properties and mechanical stability of the aluminum alloy. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with its embodiments. It should be understood that the specific implementation methods described herein are only used to explain the present invention and do not limit the protection scope of the present invention.
[0020] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0021] A method for preparing an aluminum alloy for an energy storage housing in one embodiment of the present invention comprises the following steps:
[0022] The aluminum alloy raw material is subjected to a first smelting process, and then the composite material is added, subjected to a second smelting process, and then cast into an ingot;
[0023] The ingot is subjected to extrusion treatment, stretching treatment and aging treatment to obtain an aluminum alloy for an energy storage shell;
[0024] The surface of the aluminum alloy profile is loaded with nanoparticles, and the nanoparticles have nanopores with a pore size of ≤50nm; the nanoparticles are a composite material, and the raw materials for preparing the composite material include ceramic fibers and silicon dioxide in a mass ratio of (1-5): (1-7).
[0025] In one of the embodiments, the aluminum alloy raw material includes the following chemical components in mass percentage: Si: 0.2%~0.5%, Fe: 0.10%~0.14%, Cu: 0.1%~0.3%, Mn: 1.0%~1.2%, La: 0.01%~0.03%, Zn: ≤0.1%, single impurity ≤0.05%, total impurities ≤0.15%, and the balance is aluminum.
[0026] In one embodiment, the temperature of the first smelting treatment is 720° C. to 780° C., and the time is 10 min to 15 min.
[0027] In one embodiment, the temperature of the second smelting treatment is 700° C. to 750° C., and the time is 1 min to 5 min.
[0028] In one of the embodiments, the casting temperature is 650°C to 700°C, the casting speed is 35mm / min to 45mm / min, the casting cooling water pressure is 0.05MPa to 0.1MPa, and the cooling water temperature is 20°C to 25°C.
[0029] In one of the embodiments, the extrusion barrel temperature of the extrusion process is 435°C to 450°C, and the extrusion die heating temperature is 490°C to 510°C.
[0030] In one embodiment, the reduction rate of the stretching process is 40% to 45%.
[0031] In one embodiment, the aging treatment is carried out at a temperature of 160±5°C and for a time of 8h to 10h.
[0032] In one embodiment, the preparation method of the composite material is: adding a mixture of ceramic fiber and silica to a silane coupling agent, stirring evenly, adding hexadecyltrimethylammonium bromide, and ultrasonically shaking, then controlling the temperature to 45°C to 65°C, standing for 1h to 2h, and then filtering, drying the solid at 65°C to 85°C for 15min to 30min, calcining at 500°C to 600°C for 1h to 3h, and ball milling to obtain a composite material.
[0033] In one embodiment, both the ceramic fiber and the silica have nanopores.
[0034] In one embodiment, the addition ratio of the mixture to the silane coupling agent is (1 g to 3 g) / 15 mL.
[0035] In one embodiment, the mass ratio of the mixture to the hexadecyltrimethylammonium bromide is (1-5):(1-3).
[0036] In one embodiment, the ultrasonic oscillation treatment lasts for 10 min to 15 min, the frequency is 25 kHz to 30 kHz, and the power is 50 W to 70 W.
[0037] In one embodiment, the particle size of the composite material is 50nm to 80nm.
[0038] In one of the embodiments, the mass ratio of the composite material to the aluminum alloy raw material is (10-20):100.
[0039] In one embodiment, the wall thickness of the aluminum alloy used for the energy storage shell is 0.5 mm to 0.8 mm.
[0040] In the above scheme, by adding composite materials into the aluminum alloy melt, and limiting the main components of the composite materials to ceramic fibers and silicon dioxide, it can be combined with the aluminum alloy and extend to the surface of the aluminum alloy profile, which can not only significantly increase the thermal conductivity of the aluminum alloy, but also help to improve the strength of the aluminum alloy.
[0041] The embodiments of the present invention will be described in detail below with reference to specific examples.
[0042] Embodiment 1:
[0043] A method for preparing an aluminum alloy for an energy storage housing comprises the following steps:
[0044] According to the addition ratio of the mixture to the silane coupling agent of 3g / 15mL, a mixture of ceramic fiber and silica (ceramic fiber and silica in a mass ratio of 3:7) both having nanopores is added to the silane coupling agent, and after being evenly stirred, hexadecyltrimethylammonium bromide is added in a mass ratio of the mixture to the hexadecyltrimethylammonium bromide of 1:3, and ultrasonic oscillation treatment is performed for 10 minutes at a frequency of 25kHz and a power of 50W, and then the temperature is controlled to 45°C, and the mixture is allowed to stand for 2 hours, and then filtered, the solid is dried at 65°C for 15 minutes, calcined at 500°C for 2 hours, and ball milled to obtain a composite material with a particle size of 50nm;
[0045] The aluminum alloy raw material is subjected to a first smelting treatment at 720° C. for 10 minutes, and then a composite material accounting for 10% of the weight of the aluminum alloy raw material is added, and a second smelting treatment is performed at 700° C. for 5 minutes, and then cast into an ingot under the conditions of a casting temperature of 650° C., a casting speed of 40 mm / min, a casting cooling water pressure of 0.05 MPa, and a cooling water temperature of 20° C.;
[0046] The ingot was extruded at an extrusion barrel temperature of 435° C. and an extrusion die heating temperature of 490° C., then stretched at a reduction rate of 40%, and then aged at a temperature of 165° C. for 8 hours to obtain an aluminum alloy for energy storage shell with a wall thickness of 0.5 mm.
[0047] Among them, the aluminum alloy raw material described in Example 1 includes the following chemical components in mass percentage: Si: 0.2%, Fe: 0.12%, Cu: 0.1%, Mn: 1.0%, La: 0.01%, Zn: 0.03%, single impurity ≤0.05%, total impurities ≤0.15%, and the balance is aluminum.
[0048] Embodiment 2:
[0049] A method for preparing an aluminum alloy for an energy storage housing comprises the following steps:
[0050] According to the addition ratio of the mixture to the silane coupling agent of 2g / 15mL, a mixture of ceramic fiber and silica (ceramic fiber and silica in a mass ratio of 4:7) both having nanopores is added to the silane coupling agent, and after being evenly stirred, hexadecyltrimethylammonium bromide is added in a mass ratio of the mixture to the hexadecyltrimethylammonium bromide of 1:2, and ultrasonic oscillation treatment is performed for 15min at a frequency of 30kHz and a power of 55W, and then the temperature is controlled to 60°C, and the mixture is allowed to stand for 2h, and then filtered, the solid is dried at 70°C for 20min, calcined at 550°C for 3h, and ball milled to obtain a composite material with a particle size of 50nm;
[0051] The aluminum alloy raw material is subjected to a first smelting treatment at 720° C. for 15 minutes, and then a composite material accounting for 15% of the weight of the aluminum alloy raw material is added, and a second smelting treatment is performed at 720° C. for 5 minutes, and then an ingot is cast under the conditions of a casting temperature of 650° C., a casting speed of 42 mm / min, a casting cooling water pressure of 0.06 MPa, and a cooling water temperature of 25° C.;
[0052] The ingot was extruded at an extrusion barrel temperature of 440°C and an extrusion die heating temperature of 500°C, then stretched at a reduction rate of 45%, and then aged at a temperature of 165°C for 9 hours to obtain an aluminum alloy for energy storage shell with a wall thickness of 0.6 mm.
[0053] Among them, the aluminum alloy raw material described in Example 1 includes the following chemical components in mass percentage: Si: 0.3%, Fe: 0.10%, Cu: 0.2%, Mn: 1.2%, La: 0.02%, Zn: 0.02%, single impurity ≤0.05%, total impurities ≤0.15%, and the balance is aluminum.
[0054] Embodiment 3:
[0055] A method for preparing an aluminum alloy for an energy storage housing comprises the following steps:
[0056] According to the addition ratio of the mixture to the silane coupling agent of 3g / 15mL, a mixture of ceramic fiber and silica (ceramic fiber and silica in a mass ratio of 5:7) both having nanopores is added to the silane coupling agent, and after being evenly stirred, hexadecyltrimethylammonium bromide is added in a mass ratio of the mixture to the hexadecyltrimethylammonium bromide of 2:3, and ultrasonic oscillation treatment is performed for 10min at a frequency of 30kHz and a power of 70W, and then the temperature is controlled to 45°C, and the mixture is allowed to stand for 1h, and then filtered, the solid is dried at 65°C for 15min, calcined at 600°C for 1h, and ball milled to obtain a composite material with a particle size of 50nm;
[0057] The aluminum alloy raw material is subjected to a first smelting treatment at 720° C. for 12 minutes, and then a composite material accounting for 20% of the weight of the aluminum alloy raw material is added, and a second smelting treatment is performed at 720° C. for 5 minutes, and then an ingot is cast under the conditions of a casting temperature of 650° C., a casting speed of 45 mm / min, a casting cooling water pressure of 0.1 MPa, and a cooling water temperature of 25° C.;
[0058] The ingot was extruded at an extrusion barrel temperature of 450° C. and an extrusion die heating temperature of 510° C., then stretched at a reduction rate of 45%, and then aged at a temperature of 165° C. for 10 hours to obtain an aluminum alloy for energy storage shell with a wall thickness of 0.5 mm.
[0059] Among them, the aluminum alloy raw material described in Example 1 includes the following chemical components in mass percentage: Si: 0.2%, Fe: 0.13%, Cu: 0.3%, Mn: 1.0%, La: 0.01%, Zn: 0.03%, single impurity ≤0.05%, total impurities ≤0.15%, and the balance is aluminum.
[0060] Comparative Example 1:
[0061] The difference between Comparative Example 1 and Example 3 is that the composite material in Comparative Example 1 is replaced by a single ceramic fiber, and the rest is the same as Example 3.
[0062] Comparative Example 2:
[0063] The difference between Comparative Example 2 and Example 3 is that the composite material in Comparative Example 2 is replaced by single silicon dioxide, and the rest is the same as Example 3.
[0064] Comparative Example 3:
[0065] The difference between Comparative Example 3 and Example 3 is that no composite material is added in Comparative Example 3, and the rest is the same as Example 3.
[0066] Comparative Example 4:
[0067] The difference between Comparative Example 4 and Example 3 is that the ceramic fiber and silica in Comparative Example 4 do not have nanopores, and the rest is the same as Example 3.
[0068] Comparative Example 5:
[0069] The difference between Comparative Example 5 and Example 3 is that the mass ratio of ceramic fiber to silicon dioxide in Comparative Example 5 is 1:11, and the rest is the same as Example 3.
[0070] Comparative Example 6:
[0071] The difference between Comparative Example 6 and Example 3 is that the mass ratio of ceramic fiber to silicon dioxide in Comparative Example 6 is 11:1, and the rest is the same as Example 3.
[0072] Comparative Example 7:
[0073] The difference between Comparative Example 7 and Example 3 is that the preparation method of the composite material in Comparative Example 7 is as follows: ceramic fiber and silicon dioxide are uniformly mixed in a mass ratio of 5:7, and ball milling is performed to obtain a composite material with a particle size of 50 nm. The rest is the same as Example 3.
[0074] The performance of the aluminum alloy samples for energy storage housings prepared in Examples 1 to 3 and the comparative samples prepared in Comparative Examples 1 to 7 were tested, and the results are shown in Table 1 below.
[0075] Table 1: Performance results
[0076]
[0077]
[0078] From the data analysis of Table 1, it can be seen that the present invention optimizes the composition and ratio of the composite material and adds it to the preparation of the aluminum alloy, thereby obtaining an aluminum alloy with excellent mechanical properties and significant thermal conductivity, which meets the use requirements of the energy storage shell for mechanical properties and thermal conductivity.
[0079] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0080] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing an aluminum alloy for an energy storage housing, characterized in that: The preparation method comprises the following steps: The aluminum alloy raw material is subjected to a first smelting process, and then the composite material is added, subjected to a second smelting process, and then cast into an ingot; The ingot is subjected to extrusion treatment, stretching treatment and aging treatment to obtain an aluminum alloy for an energy storage shell; The surface of the aluminum alloy profile is loaded with nanoparticles, and the nanoparticles have nanopores with a pore size of ≤50nm; the nanoparticles are a composite material, and the raw materials for preparing the composite material include ceramic fibers and silicon dioxide in a mass ratio of (1-5): (1-7).
2. The preparation method according to claim 1, characterized in that: The aluminum alloy raw material includes the following chemical components in mass percentage: Si: 0.2% to 0.5%, Fe: 0.10% to 0.14%, Cu: 0.1% to 0.3%, Mn: 1.0% to 1.2%, La: 0.01% to 0.03%, Zn: ≤0.1%, single impurity ≤0.05%, total impurities ≤0.15%, and the balance is aluminum.
3. The preparation method according to claim 1, characterized in that: The temperature of the first smelting treatment is 720° C. to 780° C., and the time is 10 min to 15 min.
4. The preparation method according to claim 1, characterized in that: The temperature of the second smelting treatment is 700° C. to 750° C., and the time is 1 min to 5 min.
5. The preparation method according to claim 1, characterized in that: The casting temperature is 650°C to 700°C, the casting speed is 35mm / min to 45mm / min, the casting cooling water pressure is 0.05MPa to 0.1MPa, and the cooling water temperature is 20°C to 25°C.
6. The preparation method according to claim 1, characterized in that: The extrusion barrel temperature of the extrusion process is 435°C to 450°C, and the extrusion die heating temperature is 490°C to 510°C.
7. The preparation method according to claim 1, characterized in that: The reduction ratio of the stretching process is 40% to 45%.
8. The preparation method according to claim 1, characterized in that: The temperature of the aging treatment is 160±5° C., and the time is 8 h to 10 h.
9. The preparation method according to claim 1, characterized in that: The preparation method of the composite material is as follows: adding a mixture of ceramic fiber and silicon dioxide to a silane coupling agent, stirring evenly, adding hexadecyltrimethylammonium bromide, performing ultrasonic oscillation treatment, then controlling the temperature to 45°C to 65°C, standing for 1h to 2h, and then filtering, drying the solid at 65°C to 85°C for 15min to 30min, calcining at 500°C to 600°C for 1h to 3h, and ball milling to obtain the composite material.
10. The preparation method according to claim 8, characterized in that: The ultrasonic oscillation treatment lasts for 10 min to 15 min, the frequency is 25 kHz to 30 kHz, and the power is 50 W to 70 W.
